(untitled) (Annals of Medical Research, 2021)
Aim: Inflammatory markers that may be associated with on the prognosis of acute ischemic stroke (IS) such as C-reactive protein/albumin ratio, neutrophil/lymphocyte ratio, albumin, red blood cell distribution width (RDW) have been investigated in the recent years. In this study, it was aimed to investigate the effects of all these inflammatory markers on in-hospital mortality and to determine the mortality rates due to cerebral artery occlusion in patients with acute IS. Materials and Methods: Patients hospitalized in our hospital with a diagnosis of acute IS between April 2014 and August 2018 were retrospectively analyzed. Logistic regression analysis was used to investigate the prognostic factors in IS. Receiver operating characteristic (ROC) curve analysis was performed to calculate the cut-off values and evaluate the predictive values of variables. Results: 344 patients, including 267 patients who were alive and 77 patients who died at the hospital, were included in the study. The infarcts that had the highest mortality rate were massive infarcts in the internal carotid artery area (75%), middle cerebral artery-M1 segment infarctions (62.5%) and total basilar artery infarcts (40%). According to the multivariate logistic regression model, only RDW-SD and albumin were found to be poor prognostic factors of IS (p=0.005 and p=0.021). Area under the ROC curve was as follows: RDW-SD 0.613 (95% CI, 0.53-0.69).Conclusions: High RDW-SD and low albumin levels at admission are independent poor prognostic factors of acute IS. Multicenter studies conducted with large patient populations are necessary to determine vascular mortality rates in patients with IS.